Verbes supports? — quelques réflexions sur la pertinence du terme - Czekaj, Anna (Neophilologica, 2013)
The article focuses on the very often discussed issue concerning the so called support verbs. Starting with one of the first definitions of support verbs, the author carries out the analsis of the evolution of the term based on the object-oriented approach. The comparison to the logical approach proposed by Stanisław Karolak is also conducted. The analysis of the chosen examples makes the author to give some thought to the legitimacy of the use of the term “support verb” in some cases.